Corrosion monitoring on different metallurgy by means of sample test in a water circuit. A pilot plant experience. (18th August 2006) - Erdmann, Eleonora; Ale Ruiz, Liliana; Riveros Zapata, Adolfo; Serrano, Emilio
One of the most used methods in the industry for corrosion monitoring is monitoring by means of sample test (coupons) in a sample test station (STS). Through the STS, a flow fraction circulates and the fluid makes permanent contact with the (coupons) in current flow for a certain period of time. The coupons, STS and flow speed are set to a standard. The material of the coupons has to be similar to the equipment's metallurgic and conduction lines that are to be measured for corrosion. Monitoring is fulfilled to quantify material loss due to corrosive phenomena or bio-corrosives to identify deposition phenomena. Corrosion is measured in mpy and deposition in mpd.